Synchronous control of two counter-rotating eccentric rotors in nonlinear coupling vibration system. (1st January 2019) - Huang, Zhilong; Song, Guiqiu; Li, Yiming; Sun, Mengnan
Highlights: The model of nonlinear vibrating system excited by two eccentric rotors is developed. Controlled synchronization of the nonlinear vibrating system is implemented by the CCC strategy and AGSMC algorithm. The speed and phase synchronization performance of nonlinear vibration system are analyzed. The influence of parameter perturbation on the system is analyzed under the condition of material nonlinear force. Abstract: In this paper, the problem of speed and phase synchronization control of two eccentric rotors (ERs) driven by asynchronous motors in a nonlinear vibration system (NVS) with nonlinear time-varying load torque is investigated. The electromechanical dynamic coupling model of NVS is established, in which the complex control of the electromechanical coupling model converts to speed and phase synchronization control of two ERs. A precise control method of speed and phase synchronization of ERs for NVS is proposed. Design the speed and phase synchronization controller by cross-coupling control (CCC) strategy and adaptive global sliding mode control (AGSMC) algorithm. The controller stability is verified by Lyapunov theorem and Barbalat lemma. The performance of the proposed control system is proved by simulation analysis and compared with the traditional self-synchronization method. The results show that the proposed control system considering the cross-coupling characteristics of ERs can effectively control the speed and phase synchronization of two ERs in NVS. The proposed control method can reduce the chattering clearly and improve the control precision. The influence of the nonlinear force of the material on the vibration system is analyzed. The influence of reference speed and parameter perturbation on the synchronization performance is discussed, and the proposed controller is proved with strong robustness. The proposed control system considering the cross-coupling characteristics of ERs can make the NVS implement stable linear vibration locus in the working direction.